A Multivariate Morphometric Analysis of the Solidago chilensis Group in South America and Related Taxa in North America (Asteraceae, Astereae) - Lopez Laphitz, Rita Maria (2015)
A multivariate morphometric study of the Solidago in South America was undertaken to assess the numbers and ranks of taxa that could be usefully recognized. The results of stepwise discriminant, classificatory, and canonical analyses on a matrix of 50 traits by 160 specimens indicated the distinctiveness of the S. chilensis group of taxa from three morphologically similar North American species of the large S. subsect. Triplinerviae (Torr. & A. Gray) G. L. Nesom, S. juliae G. L. Nesom, S. leavenworthii Torr. & A. Gray, and S. tortifolia Elliott. Within the South American complex two species with predominantly allopatric distributions were statistically supported, S. chilensis Meyen and S. microglossa DC. were distinguished a priori on stem hair length. The cytogeography of the two species was investigated and all samples were diploid, 2n = 18; S. chilensis (20 individuals from Argentina, and one from Chile) and S. microglossa (six individuals from Argentina). Also, two other species of Solidago L. in South America that are not members of S. subsect. Triplinerivae were found to have been misidentified as members of the S. chilensis complex; European S. virgaurea L. is a member of the S. subsect. Solidago and native S. argentinensis López Laphitz & Semple is a member of the S. subsect. Junceae (Rydb.) G. L. Nesom. The name Solidago chilensis Meyen is neotypified.